Strategi Orang Tua dalam Meningkatkan Disiplin Belajar pada Anak Usia Remaja di Desa Tanggungan Kecamatan Ngraho Kabupaten Bojonegoro - Al Irfiana, Tsalisatul Mustafidah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research aims to identify the factors behind the lack of learning discipline in teenage children and analyze parents' strategies in improving learning discipline in teenage children in Dependan Village, Ngraho District, Bojonegoro Regency. This research uses strategy theory from Fred R. David. with a qualitative research method, case study approach. The data collection techniques are observation, interviews and documentation with parent informants and teenage children (15-18 years) who are the research subjects. The research results show that the factors behind the lack of learning discipline in teenagers include the negative influence of peer interactions, addiction to gadgets and social media, psychological factors, parental educational background, lack of self-confidence, and the absence of sanctions and rewards from parents. The strategies used by parents include providing routine and continuous advice, providing motivation and understanding the importance of choosing peers, applying balanced and consistent sanctions and appreciation, advising children to do positive things, and accompanying the child's learning process. Implementation of effective strategies by parents has a positive impact on improving adolescent learning discipline.